MENDETEKSI PLAT NOMOR KENDARAAN DENGAN METODE YOLO (You Only Look Once) DAN SINGLE SHOT DETECTOR (SSD). - Marcellino Jonathan; Muhammad Thoriqul Hafidz; Nur Ayu Apriyanti; Zaid Husaini; Perani Rosyani (AI dan SPK : Jurnal Artificial Intelligent dan Sistem Penunjang Keputusan, 2023)
Rapid technological advancements have led to significant progress in the development of artificial intelligence (AI) on a large scale. AI technology plays various roles and offers numerous benefits depending on the specific system being utilized. One such application is text and image recognition, particularly in the context of analyzing images and videos. A notable example is the recognition of objects and text present on license plates. In this particular study, a system was designed to incorporate the You Only Look Once (YOLO) V3 algorithm as an object recognition algorithm, and Tesseract optical character recognition (OCR) for text detection within images. The system design was supported by the OpenCV library in the Python programming language, as well as the utilization of readily available image datasets. The primary objective of this study was to assess the accuracy of the implemented system in performing license plate recognition. The combination of the You Only Look Once (YOLO) V3 algorithm and Tesseract's optical character recognition (OCR)